SOME QUESTIONS OF IMPROVEMENTEXECUTION SYSTEMS (Journal of actual problems of jurisprudence, 2019)
And the second one in this article establishes the need to review prison policies in our country, what pushes a difficult situation in thedomestic penal system. And offers to eliminate this drawback, a set of additional measures in the field of human rights